Hubungan Tingkat Pengetahuan Orangtua Tentang Merokok dengan Kejadian Infeksi Saluran Pernapasan Akut (Ispa) pada Balita di Wilayah Kerja Puskesmas Gunungsari Cirebon - Iyant Yudi Gymnasti Mahardika; Eni Suhaeni; Siti Maria Ulfah (Jurnal Kesehatan Amanah, 2026)
Acute respiratory infections (ARIs) are a major cause of morbidity and mortality from communicable diseases globally. According to the WHO in 2022, ARIs contributed to nearly 14% of under-five deaths worldwide. Smoking, the leading preventable cause of death, was linked to 1.3 million deaths in 2023 due to secondhand smoke exposure, with nearly 1.2 million (about 90%) occurring in low- and middle-income countries. Knowledge significantly influences behavior, as individuals with better understanding are more likely to take appropriate preventive actions This study aims to identify the relationship between parental knowledge of smoking and the incidence of acute respiratory infections (ARIs) in toddlers in the Gunungsari Cirebon Health Center area. A quantitative cross-sectional observational study was conducted. A non-probability sampling technique, specifically quota sampling, was used to obtain a sample of 57 participants. Spearman’s rank correlation test was applied for statistical analysis. The results showed that the majority of parents had a moderate level of knowledge about smoking (61.4%). The p-value (2-tailed) was 0.091, indicating that there was no significant relationship between parental knowledge of smoking and the incidence of ARIs in toddlers. In conclusion, parental knowledge of smoking was not significantly associated with ARI occurrence in toddlers in the Gunungsari Cirebon Health Center area.